The Creator Mindset : 92 tools to unlock the secrets to innovation, growth, and sustainability - Bashan, Nir (McGraw Hill-Ascent Audio, 2021)
From B-school through the big leagues, the business world often places value on logic and analysis. But on creativity? Not so much. And this, according to Nir Bashan, is a recipe for disaster. What gets the ball rolling when we're feeling stuck in our careers? Why is my company not growing or reaching higher levels of profitability? What's the difference between a workable plan and a stroke of genius?The answer is creativity--and it's the missing ingredient for far too many of us who feel we're not reaching our creative potential. In The Creator Mindset, Bashan shows you how to use creativity as a decision-making tool and do so every bit as confidently as you use spreadsheets and data analysis. Bashan demystifies the process of sharpening this ability by breaking it down into four essential sections. Discover what is meant by a "creator mindset", why it's crucial in business, how to see the world with this mindset, and how to sustain it. Written in plain language with real-world examples, chapters include: creativity for noncreative people; training your mind to think in a creative way; when nothing else works--creativity will; envisioning a world that can be, not the world that is; the virtues of listening--and the value of making mistakes; the "Creator Mindset" guide to crisis; and beating the complacency conundrum